Dimensionality and consequences of service innovation: An empirical study of hospitality industry - Dada Ab Rouf Bhat; Vivek Sharma (Cogent Business & Management, 2021)
Based on service dominant logic (SDL) and resource-based view (RBV), this study investigates the impact of service innovation-underlying dimensions, namely, technological innovation, organizational innovation and human capital innovation on market performance and employee productivity in the hospitality industry. The study also validates and confirms the multidimensionality of service innovation in the hospitality industry. Perceptions of 400 hotel managers were used to explore the relationship. Exploratory factor analysis and confirmatory factor analysis followed by structured equation modeling were employed to examine the data. The empirical results indicate that the three-dimensional model provides a solid foundation and accomplishes an excellent fit for data. Empirical results suggest that service innovation has an influential impact on market performance. Similarly, results demonstrate that service innovation has a positive influence on employee productivity. These findings offer insight into dimensionality and consequences of service innovation for academic research and bring value to service contexts particularly hospitality.
Keywords: 330; Service innovation; Organizational innovation; Technological innovation; Market Performance; Employee Productivity; Hospitality Management